2015
DOI: 10.1002/2015gl063218
|View full text |Cite
|
Sign up to set email alerts
|

Slow electron phase space holes: Magnetotail observations

Abstract: We report multispacecraft observations of slow electrostatic solitary waves in the plasma sheet boundary layer. The electrostatic solitary waves are embedded in a region with field‐aligned electron flows and are interpreted as electron phase space holes. We make unambiguous velocity and length estimates of the electron holes, vEH∼500 km/s and l||∼2–4λDe, where l|| is the parallel half width. We do not detect any magnetic signature of the holes. The electrostatic potentials of the holes are of the order eϕ/kBTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 25 publications
2
62
0
Order By: Relevance
“…We have used multispacecraft interferometry to estimate the EH velocities and direction of propagation. Previous multispacecraft interferometry analyses have been restricted to two spacecraft and required assumptions on the direction of EH propagation (Norgren et al, ; Pickett et al, ). Using the multispacecraft interferometry we have found that the EHs propagate quasi‐parallel to the magnetic field with velocities of a few thousands of kilometers per second and have parallel spatial scales of a few Debye lengths.…”
Section: Discussionmentioning
confidence: 99%
“…We have used multispacecraft interferometry to estimate the EH velocities and direction of propagation. Previous multispacecraft interferometry analyses have been restricted to two spacecraft and required assumptions on the direction of EH propagation (Norgren et al, ; Pickett et al, ). Using the multispacecraft interferometry we have found that the EHs propagate quasi‐parallel to the magnetic field with velocities of a few thousands of kilometers per second and have parallel spatial scales of a few Debye lengths.…”
Section: Discussionmentioning
confidence: 99%
“…The generation mechanism of such EHs is likely an electron beam instability [ Morse and Nielson , ; Omura et al , ; Goldman et al , ]. Norgren et al [] and Graham et al [] have also reported observations of much slower EHs likely generated by the Buneman instability.…”
Section: Discussionmentioning
confidence: 99%
“…The primary axis false(trueẑfalse) is chosen parallel to B 0 . This particular model has the advantages of straightforward integration and distinct parallel and perpendicular length scales and has been successfully applied to both theory and observations in several instances (Andersson et al, ; Chen et al, , ; Norgren et al, ; Tao et al, ), so those results can be compared easily. normalΦfalse(r,zfalse)=Φ0er22L2ez22L2 …”
Section: Analytic Modelmentioning
confidence: 99%